Implementasi Model Pembelajaran Berbasis Proyek Pada Mata Pelajaran Bahasa Jawa (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to explain the implementation of the project-based learning model in Javanese language subjects. Descriptive qualitative method was used as a step in this research. The data in the research was collected through interview, observation and documentation techniques. The data analysis technique used by Miles and Huberman is in steps 1) data is collected, 2) data is reduced, 3) data is presented, and 4) data is concluded. Informants include school principals, teachers and students. The result of this research is that this project-based learning model was implemented for wayang material. This PjBL model is named Ngenger. Ngenger is carried out by preparing class VII students, preparing a schedule of Ngenger activities, supervising the implementation of Ngenger, assessing students, and conducting an evaluation of the implementation of Ngenger.